2018
DOI: 10.1371/journal.pone.0206813
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Bacillus thuringiensis isolates by their insecticidal activity and their production of Cry and Vip3 proteins

Abstract: Bacillus thuringiensis (Bt) constitutes the active ingredient of many successful bioinsecticides used in agriculture. In the present study, the genetic diversity and toxicity of Bt isolates was investigated by characterization of native isolates originating from soil, fig leaves and fruits from a Turkish collection. Among a total of 80 Bt isolates, 18 of them were found carrying a vip3 gene (in 23% of total), which were further selected. Insecticidal activity of spore/crystal mixtures and their supernatants sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 50 publications
5
14
0
Order By: Relevance
“…To better understand the three-dimensional organization and activation mechanism of these toxins, purified Vip3Aa was applied to electron microscopy grids coated with a thin carbon layer and analyzed using cryo-EM. The reference-free 2D averages of the motion-corrected micrographs show, in agreement with previous reports, the tetrameric organization of the protoxin 12 , 15 , 21 24 (Fig. 1 , Supplementary Figs.…”
Section: Resultssupporting
confidence: 91%
“…To better understand the three-dimensional organization and activation mechanism of these toxins, purified Vip3Aa was applied to electron microscopy grids coated with a thin carbon layer and analyzed using cryo-EM. The reference-free 2D averages of the motion-corrected micrographs show, in agreement with previous reports, the tetrameric organization of the protoxin 12 , 15 , 21 24 (Fig. 1 , Supplementary Figs.…”
Section: Resultssupporting
confidence: 91%
“…The identified protein, named Vip3Aa65, has a similar insecticidal activity against Grapholita molesta (Lepidoptera: Tortricidae) and H. armigera, but is less toxic to Spodoptera spp. compared with Vip3Aa16 [ 85 ]. In another study, two Bt strains, BnBt and MnD, were found to produce Vip proteins in isolates of great potential with a high toxicity (LC 50 = 41.860 ng/μL of BnBt and 55.154 ng/μL of MnD) in the second instar larvae of S. littoralis [ 86 ].…”
Section: Identification Of Bt Isolates Containing Vip Genesmentioning
confidence: 99%
“…Then, two peptides, of about 19 and 65 kDa, are generated, and these remain strongly bound to each other [3,6,7]. More recently, it has been shown that Vip3 proteins are found in solution as homo-tetramers, both as protoxins and after activation by proteases [3,7,8,9].…”
Section: Introductionmentioning
confidence: 99%